2017
DOI: 10.1177/1744806917737462
|View full text |Cite
|
Sign up to set email alerts
|

Propofol produces preventive analgesia via GluN2B-containing NMDA receptor/ERK1/2 signaling pathway in a rat model of inflammatory pain

Abstract: Propofol, an intravenous anesthetic, has been shown to offer superior analgesic effect clinically. Whether propofol has preventive analgesic property remains unexplored. The present study investigated the antinociceptive effect of propofol and underlying molecular and cellular mechanisms via pre-emptive administration in a formalin-induced inflammatory pain model in rats. Male adult Sprague–Dawley rats were randomly allocated into four groups: naïve (Group Naïve), formalin injection only (Group Formalin), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…In this study, icaritin eventually played a neuroprotective role by regulating the expression and/or activation of DAPK1, GluN2B and GluN2A. Some studies indicated that GluN2B/CaMKII could regulate the activation of ERK in the upstream of ERK ( Cao et al, 2012 ; El Gaamouch et al, 2012 ; Melgarejo et al, 2016 ; Qiu et al, 2017 ; Buonarati et al, 2020 ). DAPK1 could bind to GluN2B regions, which required allosteric regulation of CaMKII ( Cao et al, 2012 ; Goodell et al, 2017 ; Tu et al, 2018 ; Buonarati et al, 2020 ).…”
Section: Discussionmentioning
confidence: 67%
“…In this study, icaritin eventually played a neuroprotective role by regulating the expression and/or activation of DAPK1, GluN2B and GluN2A. Some studies indicated that GluN2B/CaMKII could regulate the activation of ERK in the upstream of ERK ( Cao et al, 2012 ; El Gaamouch et al, 2012 ; Melgarejo et al, 2016 ; Qiu et al, 2017 ; Buonarati et al, 2020 ). DAPK1 could bind to GluN2B regions, which required allosteric regulation of CaMKII ( Cao et al, 2012 ; Goodell et al, 2017 ; Tu et al, 2018 ; Buonarati et al, 2020 ).…”
Section: Discussionmentioning
confidence: 67%
“…In another study, it was reported that propofol protected against LPS-mediated inflammation in primary microglial cells, and the protective effect was mediated by inhibition of NMDA receptors and the Ca 2+ /CaMKII pathway [48]. An animal study also showed that propofol inhibited the NMDA receptor/ERK signaling pathway, exerting preventive analgesia in a rat model of inflammatory pain [49]. In combining these data with our current findings, although we did not examine which receptor is responsible for the effect of propofol in this study, we believe that it is mediated by inhibition of NMDA receptors.…”
Section: Discussionmentioning
confidence: 95%
“…4,26,27,34,64 Data from rodent studies suggest that sedative doses of propofol, both 36 and 90 mg/kg/hr., are antinociceptive. 74,94 It is possible that propofol's analgesic effect in NHP could be observed at doses that are higher than that needed for stable sedation, which would be, in macaques, between 12 to 36 mg/ kg/hr. 34 The current study tested the effects of 20 and 30 mg/ kg/hr propofol on noxious stimulus-evoked brain activation.…”
Section: Methodsmentioning
confidence: 99%